Childfree In the Perspective of Islamic Law and Religious Sociology: A Study of the Fatwa of The MUI of Muara Jambi District - Sibawaihi, Muhammad; Umar, Hasbi; Mukhtar, Mukhtar; Adawiyah, Robi'atul; Muhammad, Pauzi (Jurnal Mediasas: Media Ilmu Syari'ah dan Ahwal Al-Syakhsiyyah, 2025)
The phenomenon of childfree, a couple's conscious decision to live a married life without having children, has sparked an in-depth discourse in the study of Islamic law and religious sociology in Indonesia. This polemic is increasingly prominent as open statements from well-known public figures such as Gita Savitri and Cinta Laura, which strengthen the conversation about the legitimacy and implications of this practice in the context of sharia and contemporary social dynamics. This study aims to analyze the views of the Indonesian Ulema Council (MUI) of Muara Jambi Regency on the childfree phenomenon, focusing on the factors behind it and its legal status in the perspective of Islamic law. Adopting a juridical-sociological approach with a descriptive-analytical paradigm, this research utilizes semi-structured interviews with the leadership of MUI Muara Jambi, documentation studies, and non-participant observation. The research findings identify four main factors that encourage childfree practices: psychological unpreparedness to become parents, economic concerns, socio-psychological environmental conditions, and physical health considerations.In the perspective of Islamic law, MUI Muara Jambi categorizes childfree as haram if it is only based on economic concerns, but permissible if it is supported by valid shar'i reasons, such as health risks, provided that it meets the conditions such as mutual agreement between couples and alignment with maqashid sharia. This study contributes to the development of contemporary Islamic legal discourse by offering a moderate perspective that integrates sharia principles with modern social dynamics. [Fenomena childfree, yakni keputusan sadar pasangan suami-istri untuk menjalani kehidupan perkawinan tanpa memiliki keturunan, telah memantik diskursus mendalam dalam kajian hukum Islam dan sosiologi keagamaan di Indonesia. Polemik ini kian mengemuka seiring pernyataan terbuka dari tokoh publik ternama seperti Gita Savitri dan Cinta Laura, yang memperkuat perbincangan mengenai legitimasi dan implikasi praktik tersebut dalam konteks syariah dan dinamika sosial kontemporer. Penelitian ini bertujuan untuk menganalisis pandangan Majelis Ulama Indonesia (MUI) Kabupaten Muara Jambi terhadap fenomena childfree, dengan fokus pada faktor-faktor yang melatarbelakanginya serta status hukumnya dalam perspektif hukum Islam. Mengadopsi pendekatan yuridis-sosiologis berparadigma deskriptif-analitis, penelitian ini memanfaatkan wawancara semi-terstruktur dengan pimpinan MUI Muara Jambi, studi dokumentasi, dan observasi non-partisipan. Temuan penelitian mengidentifikasi empat faktor utama yang mendorong praktik childfree: ketidaksiapan psikologis untuk menjadi orang tua, kekhawatiran ekonomi, kondisi lingkungan sosial-psikologis, dan pertimbangan kesehatan fisik. Dalam perspektif hukum Islam, MUI Muara Jambi mengkategorikan childfree sebagai haram apabila hanya didasarkan pada kekhawatiran ekonomi, namun mubah jika didukung oleh alasan syar’i yang sah, seperti risiko kesehatan, dengan syarat memenuhi ketentuan seperti kesepakatan mutual antar pasangan dan keselarasan dengan maqashid syariah. Kajian ini berkontribusi pada pengembangan diskursus hukum Islam kontemporer dengan menawarkan perspektif moderat yang mengintegrasikan prinsip syariah dengan dinamika sosial modern].